Hellenizm ve roma çağları Likyası’nda yeral kültler - Efendioğlu, Tuba (My University, 2008)
Likya, bugün Türkiye’nin güney kıyıları olan Antalya ve Muğla illerini içinde yer alan Anadolu’daki bir ülkeydi. Antik kentlerin oluşturduğu bir federasyon ve ardından Roma İmparatorluğu’nun eyaleti olarak yer almıştır. Likya, dinsel yaşamını da etkileyen coğrafi durumu ve kendine has tarihsel, kültürel ve etnik özelliklere sahip olan bir ülkeydi. Likya tanrı ve tanrıçaları hakkındaki bilgilerimiz M.ö. 5.yy sonundan M.ö. 4.yy başlangıcına kadar kaleme alınan Likya dilinde yazılmış yazıtlara dayanmaktadır. Likya tanrı ve tanrıçalarının varlığı sadece Anadolu tanrılarına değil aynı zamanda M.ö. IV. yy. sonrasında daha güçlü olmaya başlayan Hellen kültürü tanrılarına da dayanmaktadır. Hellen tanrılarının etkisine rağmen, Likyalılar Roma Çağı sonlarına dek Anadolu Tanrıları’na tebcil etmeye devam etmişlerdir. Bu çalışma 7 bölümden oluşmaktadır. Anadolu’daki Kybele kültünün devamı olarak dikkat toplayan «Ana Tanrıçalar»dır. İkinci bölüm, Likya’da tebcil edilen «Eril Tanrılar»a ayrılmıştır, üçüncü bölümde de atlı tanrı olan «Kakasbos» çalışılmıştır. Dördüncü bölümde Likya’nın «Oniki Tanrıları» ile ilgilidir. Hosios kai Dikaios’la ilişkilendirilen «Theoi Dikaioi» kültü beşinci bölümü oluşturmaktadır. «Vahşi Tanrılar» altıncı bölümü açıklığa kavuşturmakta, son bölüm ise, haklarındaki sınırlı bilgimizi yazıtlardan edindiğimiz «Yer altı Tanrıları»nı içermektedir.

Lycia was a region in Anatolia in what are now the provinces of Antalya and Muğla on the southern coast of Turkey. It was a federation of ancient cities in the region and later a province of the Roman Empire. Lycia was distinctive with respect to its geographical position and had peculiar historical, cultural and ethnical characteristics, which in combination affected its religious life. Our knowledge about Lycian gods and goddesses are based on the inscriptions in Lycian language that were written during the period from end of 5. century B.C to beginning of 4.century B.C. The presence of Lycian gods and goddesses seem to be related not only to the Anatolian gods and goddesses but also to gods of the Hellenic Culture which had become stronger after IV. B.C. Despite the influence of Hellenic gods, Lycians continued to worship Anatolian gods until the end of Roman age. This study is divided into seven chapters. The first chapter, «Ana Tanrıçalar», focuses on the, goddesses emerged following the Cybele cult in Anatolia. The second chapter, «Eril Tanrılar» provided information on the masculine divinities which were worshiped in Lycia, while a horseman god «Kakasbos» is studied in the third chapter. The four chapter «Oniki Tanrılar» deals with “the twelve gods” of Lycia. The «Theoi Dikaioi» which are associated with Hosios kai Dikaiois constitute the main subject in the fifth chapter. «Vahşi Tanrılar» or “Wild Gods” are explained the sixth chapter and the last chapter is concerned with «Yeraltı Tanrıları» or “Underground Gods” on whom our knowledge is limited with what is provided by the inscriptions.
Keywords: Eski Çağ; Hellenizm; Tarih_Roma